The use of porphyrins in potentiometric sensors as ionophores - Özbek, Oguz; Isildak, Ömer; Berkel, Caglar (Journal of inclusion phenomena and macrocyclic chemistry, 2020)
Porphyrins are a group of macrocyclic compounds which are widely used in many applications in the literature due to their multiple functions. One of their application areas is in the development of sensors which transform changes in physical and chemical parameters into electrical signals. Novel chemical sensors selective and sensitive for many anions and cations have been fabricated with the advancements in the technology. Real sample applications of these sensors can be successfully performed. In recent years, potentiometric methods have drawn researchers' attention and they have been highly studied because of their superiority over other analytical devices. Ionophores which are used in the development of potentiometric sensors and ion-selective electrodes are the most important components of these systems. Therefore, porphyrin molecules, which have favorable chemical structures, can be directly used as an active component (ionophore) in the structure of potentiometric sensors. In this review, we investigated porphyrin derivatives used as ionophore in the design of potentiometric sensors and we focused on newly developed potentiometric sensors based on porphyrin.